ANALYSIS OF CRIMINAL RESPONSIBILITY OF CRIMINAL ACTIVITIES OF THE EIGHTS AND EXTENSION OF CAR (Study of Decision Number 839/Pid.B/2018/PN.Tjk Year 2018) - Ridwan, Alan (Progressive Law Review, 2019)
One of the crimes concerning the misuse of car vehicles is the crime of embezzling cars as the crime is rampant in Indonesia, one of which is in case Number 839/Pid.B/2018/PN.Tjk in 2018. The problem in research is why the perpetrators commit criminal acts embezzlement and imposition of cars based on Decision Number 839/Pid.B/2018/PN.Tjk and how the criminal responsibility of the perpetrators of criminal acts of embezzlement and detention of cars is based on Decision Number 839/Pid.B/2018/PN.Tjk. The research method uses a normative and empirical juridical approach, the normative juridical approach is carried out by studying legal norms or rules, legal principles, while the empirical approach is carried out by direct interviews with informants who will relate to research problems, data analysis used is qualitative analysis. The results of the study indicate that the factors causing the perpetrators to commit criminal acts of embezzlement and car detention are based on Decision Number 839/Pid.B/2018/PN.Tjk opportunity factors and economic needs factors. This factor is due to the defendant's desperate need for a certain amount of money at a fast time so that the defendant made a shortcut by making embezzlement and overcoming the car. The criminal liability of the defendant who commits a crime of manipulating and imposing a car based on Case Number 839/Pid.B/2018/PN.Tjk Year 2018 is that the sentence of imprisonment for 8 (eight) months is reduced as long as the defendant is temporarily detained. detained. Suggestions, for the Judges in carrying out the consideration prioritize a sense of justice for victims, defendants and the public. In addition, judges should carefully pay attention to matters that can alleviate or incriminate defendants other than judges who have also been given the freedom to make decisions in order to enforce law and justice so that judges do not have to depend on public prosecutors' demands in determining crimes for defendants. To the Public Prosecutor in applying the criminal or in giving a claim to the defendant must be appropriate or in accordance with the actions of the defendant because this is the judge's reference in making his decision. In addition, the Public Prosecutor should also have material legal knowledge so that there are no more errors or nonconformities in applying the crime against the accused.